2015
DOI: 10.1007/s00134-015-3970-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular global longitudinal strain is independently associated with mortality in septic shock patients

Abstract: These findings suggest that combining GLS and the APACHE II score has additive value in the prediction of ICU and hospital mortalities and that GLS may help in early identification of high-risk septic shock patients in ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 40 publications
4
69
1
4
Order By: Relevance
“…STE is an operator-independent technique with low inter-observer variability (from 2 [31] to 13% [32]) regarding strain data but higher variability regarding strain rate [28]. In patients with mechanical ventilation, we found an inter-observer variability of 8% [25] while others [20,24] have also found a good inter-observer agreement with a Bland-Altman analysis. STE could, therefore, provide objective data on systolic function with an acceptable variability.…”
Section: What Could Ste Add In the Icu Field?supporting
confidence: 50%
See 1 more Smart Citation
“…STE is an operator-independent technique with low inter-observer variability (from 2 [31] to 13% [32]) regarding strain data but higher variability regarding strain rate [28]. In patients with mechanical ventilation, we found an inter-observer variability of 8% [25] while others [20,24] have also found a good inter-observer agreement with a Bland-Altman analysis. STE could, therefore, provide objective data on systolic function with an acceptable variability.…”
Section: What Could Ste Add In the Icu Field?supporting
confidence: 50%
“…LV strain could, therefore, be used in septic shock as a surrogate marker of oxygenation deliverance inadequacy. To the best of our knowledge, one study pointed out that right ventricle strain impairment was associated with long-term mortality in septic shock [20] and a large mono-centric study of 111 patients pointed out that a GLS impairment ≥ −13% was the best marker of in-ICU mortality [24]. Our group published a mono-centric observational study about LV systolic function assessment with STE in patients with severe subarachnoid haemorrhage [25].…”
Section: Speckle-tracking In the Intensive Care Unitmentioning
confidence: 99%
“…The presence of myocardial depression, defined echocardiograpically (21)(22)(23)(24)(25) or by elevations in cardiac injury/dysfunction biomarkers such as troponin or B-type natriuretic peptide (26)(27)(28), is strongly associated with an increased mortality risk in septic patients. An important limitation in experimental studies proposing a role for mitochondria in septic cardiomyopathy is that they fail to consider the heterogeneity observed in human populations where patients may/may not develop septic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown that the combination of global longitudinal strain (GLS) and the APACHE II score have additional value in the prediction of ICU and hospital mortality in septic shock patients admitted to the ICU [27]. STE may help in the early identification of high-risk patients in the ICU.…”
Section: Speckle Tracking Echocardiography (Ste)mentioning
confidence: 99%